MISOGYNISTIC HADITHS: A STUDY OF CONCEPTS AND PERCEPTIONS BASED ON THE UNDERSTANDING OF FEMALE SANTRI OF THE SALAFIYAH HIDAYATUL QOMARIYAH ISLAMIC BOARDING SCHOOL IN BENGKULU - Suryani Suryani; Agusri Fauzan; Devi Saraswati (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2024)
This study wants to examine the perception of students and their understanding of misogynistic Hadith. Santri are students who pursue Islamic religious knowledge who live in a place called Pondok Pesantren, they are a group of learners led by a kiyai who has their own scientific traditions, such as reciting the Qur'an and hadith, reciting the yellow book and other Islamic sciences. The problems raised in this study are: first, how are the hadiths that talk about women who are considered misogenist hadiths, second is how the students' understanding of misogenic hadiths, and third, how do students perceive these misogenic hadiths.This research explores the speculation that develops in understanding Hadith which is classified as misogynistic, giving rise to many opinions in understanding it, the authors consider that santri have needs and are important in knowing this issue because they are scientific agents in society. This study uses a type of qualitative field research (field research), which includes observation, interviews and documentation. The author analyzed the data using the Miles and Huberman model, namely data analysis in qualitative research conducted during data collection and after data collection was completed. Based on this research, it is known that the students of the Salafiyah Hidayatul Qomariyah Islamic Boarding School Bengkulu do not yet know the term misogynist, but many of them agree that the Hadiths are classified as misogynistic, but there are also those who oppose the existence of this misogynist term. There are some students who understand every misogynistic Hadith that is examined textually, they understand what it is according to the Hadith text, but there are those who understand contextually by including knowledge of asbabul wurud Hadith, by looking at the conditions when the Hadith appears with its use in the present.